Sliding-mode and proportional-resonant based control strategy for three-phase two-leg T-type grid-connected inverters with LCL filter - Altın, Necmi N.; Ozdemir, Saban S.; Komurcugil, Hasan; Sefa, Ibrahim; Biricik, Samet (Institute of Electrical and Electronics Engineers Inc., 2018)
In this study, sliding-mode and proportional-resonant based control strategy is proposed for three-phase two-leg T-type grid-connected inverter with LCL filter. The sliding surface function is formed by using the inverter current and capacitor voltage errors. When the inverter current and capacitor voltage feedbacks are included into the control loop, the active damping requirement is automatically resolved. The PR controllers are employed in cascaded manner to generate the references for inverter current and capacitor voltage. The use of PR controllers ensures zero steady-state error in the inverter current, capacitor voltage and grid current. In addition, since the proposed three-phase inverter has only two legs, the total switch count is reduced resulting in cheaper and reliable topology. The proposed system is validated through computer simulations which show that proposed control algorithm can achieve the control of grid currents. The total harmonic distortion level of the grid currents is in the limits of international standards. © 2018 IEEE.
44th Annual Conference of the IEEE Industrial Electronics Society, IECON 2018 -- 2018-10-20 through 2018-10-23 -- Washington -- 144100
Keywords: Grid interactive; Proportional resonant; Reduced number of switches; SMC; Two-leg